Transformation and Strategic Role of Salaf Al-Manar Islamic Boarding School in Globalization Era - Abdul Khamid; Badrus Zaman; Yuserizal Bustami; Mushbihah Rodliyatun; Ahmad MuÔÇÖis; Doli Witro (Ta'dib, 2025)
This research aims to find out the transformation in the institutionalisation of Islamic education, especially in pesantren (Islamic boarding school) Salaf. The focus of this research is on the transformation of Islamic education institutions in Salaf Islamic boarding schools, as well as their strategic role in the era of globalisation. This research uses a qualitative research method approach. This research is located at Salaf Al-Manar Islamic Boarding School in Bener Village, Tengaran District, Semarang Regency. The primary data source of this research comes from observations and interviews with relevant parties involved in various activities at the Salaf Al-Manar Islamic Boarding School. While secondary data sources are taken from some library data discussing the object of research such as articles (journals), books and other literature sources that support this research. Data collection techniques include observation, interviews, and documentation. Furthermore, the data analysis technique consists of three stages, namely data condensation, presenting data, and drawing conclusions (verification). Finally, data validity was tested by triangulating sources and triangulating techniques. This study found that first, Al-Manar Foundation underwent institutional transformation starting from the initial lodging place or pesantren and turning into Al-Manar Foundation. Second, the awakening of the fighting spirit of santri is very visible with the beginning of many santri who are considered classical/ Salaf starting to transform today in the world of formal education, even many santri continue to college level both general and Islamic. Third, the strategic role of the managers of pesantren educational institutions in the Era of Globalisation is to guard the teachings of morals and become the front guard.